Empowering Change: The Strategic Role Of Nursing Leadership In Achieving Vision 2030 Healthcare Goals (The Review of Diabetic Studies, 2025)
Nursing leadership is central to achieving sustainable healthcare transformation and aligning clinical practices with Saudi Vision 2030’s objectives for quality, efficiency, and innovation. This review explores the strategic role of nursing leaders in driving change within healthcare systems, focusing on governance, workforce development, and digital transformation. Using an integrative review methodology, recent empirical and conceptual studies (2016–2025) were analyzed to identify leadership strategies, competencies, and policy frameworks influencing healthcare improvement. Findings reveal that effective nursing leadership contributes to better patient outcomes, staff satisfaction, and organizational resilience through evidence-based decision-making and interprofessional collaboration. Moreover, Vision 2030 emphasizes empowering Saudi nurses to assume leadership positions in quality management, research, and health technology innovation. The paper concludes that investing in nursing leadership development and integrating leadership frameworks into national policies is essential for achieving long-term health sector transformation under Vision 2030.